Lessons from primary immunodeficiencies: Autoimmune regulator and autoimmune polyendocrinopathy‐candidiasis‐ectodermal dystrophy. Issue 1 (18th December 2018) - Constantine, Gregory M.; Lionakis, Michail S.
Summary: The discovery of the autoimmune regulator (AIRE) protein and the delineation of its critical contributions in the establishment of central immune tolerance has significantly expanded our understanding of the immunological mechanisms that protect from the development of autoimmune disease. The parallel identification and characterization of patient cohorts with the monogenic disorder autoimmune polyendocrinopathy‐candidiasis‐ectodermal dystrophy (APECED), which is typically caused by biallelic AIRE mutations, has underscored the critical contribution of AIRE in fungal immune surveillance at mucosal surfaces and in prevention of multiorgan autoimmunity in humans. In this review, we synthesize the current clinical, genetic, molecular and immunological knowledge derived from basic studies in Aire‐deficient animals and from APECED patient cohorts. We also outline major advances and research endeavors that show promise for informing improved diagnostic and therapeutic approaches for patients with APECED.